2023
DOI: 10.1002/admt.202301143
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent and Stable Flexible Electrodes Based on MgO/AgNW Nanocomposites for Transparent Heating Applications

Abderrahime Sekkat,
Dorina T. Papanastasiou,
Maheera Abdul Ghani
et al.

Abstract: Transparent electrodes (TE) based on silver nanowire (AgNW) exhibit good physical properties and constitute a promising alternative to transparent conductive oxides due to their low cost, flexibility, and low toxicity. Nevertheless, they suffer from stability issues over harsh conditions, and encapsulation allows to overcome these limitations. Herein, the low‐cost, scalable fabrication and study of transparent electrodes based on sprayed AgNW networks coated with MgO thin films deposited by atmospheric pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…However, further temperature increases may cause NWs to split into shorter fragments -a process often attributed to Rayleigh instability and energy minimization via spheroidization [28,31]. It has been demonstrated that various coatings can effectively protect metallic NWs by suppressing surface diffusion [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…However, further temperature increases may cause NWs to split into shorter fragments -a process often attributed to Rayleigh instability and energy minimization via spheroidization [28,31]. It has been demonstrated that various coatings can effectively protect metallic NWs by suppressing surface diffusion [32][33][34].…”
Section: Introductionmentioning
confidence: 99%